2015
DOI: 10.1002/2015jd023212
|View full text |Cite
|
Sign up to set email alerts
|

The near‐global mesospheric potassium layer: Observations and modeling

Abstract: The meteoric metal layers act as unique tracers of chemistry and dynamics in the upper atmosphere. Existing lidar studies from a few locations show that K exhibits a semiannual seasonality (winter and summer maxima), quite unlike the annual seasonality (winter maximum and summer minimum) seen with Na and Fe. This work uses spaceborne observations made with the Optical Spectrograph and InfraRed Imager System instrument on the Odin satellite to retrieve the near‐global K layer for the first time. The satellite d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 74 publications
(122 reference statements)
5
40
0
Order By: Relevance
“…Lidar observations have shown that K column abundance varies semiannually, with maxima in summer and winter and minima at the equinoxes [ Mégie et al ., ; Eska et al ., ; Friedman et al ., ]. More recently, satellite‐based observations have demonstrated that the semiannual variability is global in extent except at very high latitudes [ Dawkins et al ., , ]. Dawkins et al .…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Lidar observations have shown that K column abundance varies semiannually, with maxima in summer and winter and minima at the equinoxes [ Mégie et al ., ; Eska et al ., ; Friedman et al ., ]. More recently, satellite‐based observations have demonstrated that the semiannual variability is global in extent except at very high latitudes [ Dawkins et al ., , ]. Dawkins et al .…”
Section: Introductionsupporting
confidence: 73%
“…Dawkins et al . [] investigated the relationship between temperature and K density by employing the National Center for Atmospheric Research (NCAR) Whole Atmosphere Community Climate Model with potassium chemistry (WACCM‐K) [ Plane et al ., , ], and their results validated the temperature dependence of the Plane et al . [] K chemistry model.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the results presented here demonstrate that the unusual behavior of K compared to Na and Fe is present at diurnal [ Feng et al ., ], seasonal [ Dawkins et al ., ], and longer timescales (this study). The model predicts that K is the only one of these three metals that will provide a sensitive indicator of long‐term changes in the MLT region.…”
Section: Discussionmentioning
confidence: 56%
“…These spaceborne spectrometers typically were on board satellites with Sun-synchronous and polar orbits and a maximum scanned latitude of up to 82 • that retrieved densities for Mg and/or Mg + (see, e.g., Joiner and Aikin, 1996;Correira et al, 2008;Scharringhausen et al, 2008;Langowski et al, 2015), K (see, e.g., Dawkins et al, 2014) and Na (see, e.g., Fussen et al, 2004;Casadio et al, 2007;Fan et al, 2007;Gumbel et al, 2007;Fussen et al, 2010;Hedin and Gumbel, 2011;Langowski et al, 2016). Along with the measurements, global atmospheric models for the metal layers in the MLT have been developed for Na (Marsh et al, 2013a), Fe (Feng et al, 2013), Mg (Langowski et al, 2015), K Dawkins et al, 2015), and Si atoms, molecules and ions.…”
Section: Introductionmentioning
confidence: 99%